2016
DOI: 10.1080/21691401.2016.1220950
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles from Catharanthus roseus leaf extract and assessing their antioxidant, antimicrobial, and wound-healing activities

Abstract: Biosynthesis of silver nanoparticles (AgNPs) from Catharanthus roseus leaf extract was carried out, and their characterization, as well as antioxidant, antimicrobial, and wound-healing activities were evaluated. Color change, UV-vis spectrum, XRD, FTIR, and AFM assessments supported the biosynthesis and characterization of AgNPs. The synthesized AgNPs showed strong in vitro antioxidant and antimicrobial activities against various pathogens. The in vivo assessment of wound healing in AgNPs-treated mice revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 25 publications
5
67
0
Order By: Relevance
“…Antimicrobial actions of BSNPs exhibited dose dependency and all clearance zones can be attributed to phenols, flavonoid and alkaloids present in PCFE that capped the BSNPs [41]. Effective clearance zones for bacterial and fungal strains obtained with BSNPs make them versatile nanobactericide and fungicides [42].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial actions of BSNPs exhibited dose dependency and all clearance zones can be attributed to phenols, flavonoid and alkaloids present in PCFE that capped the BSNPs [41]. Effective clearance zones for bacterial and fungal strains obtained with BSNPs make them versatile nanobactericide and fungicides [42].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such functional groups increased the stability of the synthesized nanoparticles by preventing the clotting and aggregation of the nanoparticles. The similarities between the spectra, before and after synthesis of nanoparticles, with some marginal shifts in peak positions indicated the presence of residuals from the different plant extracts in the sample which acted as a capping agent to the synthesized AgNPs [44,47]. Therefore, it can be concluded that these secondary metabolites are responsible for the effective stabilization and capping of the synthesized nanoparticles.…”
Section: Characterization Of Agnps Using Ftirmentioning
confidence: 90%
“…The antioxidant activity was determined by using DPPH according to Al-Shmgani et al [31]. Briefly, 1 mL of the samples was mixed with an equal volume of the DPPH solution (60 µM).…”
Section: Hesperidin Antioxidant Activity Measurementmentioning
confidence: 99%